Me and My Secrets: A Phenomenological Study of Communication Privacy Management of Atheists in the Indonesian Context Regarding Their Identity - Azzumar Adhitia Santika; Rudi Sukandar (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2023)
Being an Atheist is always an unpopular choice in the middle of high religious context society. The stigma and pressure from religious groups forced Atheists in Indonesia to hide their identity in public generally and when taking care of the affairs of state administration. This research utilized Communication Privacy Management and Dramaturgy Theory alongside the phenomenology perspective to reveal how Atheists in Indonesia live their "beliefs" in their not-so-friendly environment. The results showed that they generally presented themselves as religious in front of their family by pretending to practice religious rituals, contributing to their special personal branding for the families. Meanwhile, in other social environments, such as friendship, they could be freer to present themselves as they were, although they still had to manage private information about their Atheist identity.